2020
DOI: 10.3390/genes11111352
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Structure of Chinese Hui Ethnic Group Revealed by Complete Mitochondrial Genome Analyses Using Massively Parallel Sequencing

Abstract: Mitochondrial DNA (mtDNA), coupled with maternal inheritance and relatively high mutation rates, provides a pivotal way for us to investigate the formation histories of populations. The Hui minority with Islamic faith is one of the most widely distributed ethnic groups in China. However, the exploration of Hui’s genetic architecture from the complete mitochondrial genome perspective has not been detected yet. Therefore, in this study, we employed the complete mitochondrial genomes of 98 healthy and unrelated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 49 publications
5
13
1
Order By: Relevance
“…In addition to the reference Hui groups from Chinese different regions, the Northwest Hui group depicted using Y-STRs was more prone to display closer genetic relationships with populations from Central and West Asia, as well as several Chinese groups. Additionally, our previous research based on the complete mitochondrial genome illustrated that the Northwest Hui group typically exhibited closer genetic relationships with East Asian populations, roughly concordant with the genetic result provided by 55 AISNPs in this study (Chen et al, 2020). Briefly, our previous study indicated that the genetic component of the maternal lineage that appeared in the Northwest Hui group might be predominantly derived from East Asia (Chen et al, 2020); the Y chromosome strictly follows the paternal inheritance with little recombination during the genetic process, so the paternal lineage of the Northwest Hui group may still retain some ancient genetic imprints closely related to Central or West Asian populations (Gladney, 1998).…”
Section: Ancestral Components Of the Northwest Hui Group Revealed Using Aisnpssupporting
confidence: 90%
See 4 more Smart Citations
“…In addition to the reference Hui groups from Chinese different regions, the Northwest Hui group depicted using Y-STRs was more prone to display closer genetic relationships with populations from Central and West Asia, as well as several Chinese groups. Additionally, our previous research based on the complete mitochondrial genome illustrated that the Northwest Hui group typically exhibited closer genetic relationships with East Asian populations, roughly concordant with the genetic result provided by 55 AISNPs in this study (Chen et al, 2020). Briefly, our previous study indicated that the genetic component of the maternal lineage that appeared in the Northwest Hui group might be predominantly derived from East Asia (Chen et al, 2020); the Y chromosome strictly follows the paternal inheritance with little recombination during the genetic process, so the paternal lineage of the Northwest Hui group may still retain some ancient genetic imprints closely related to Central or West Asian populations (Gladney, 1998).…”
Section: Ancestral Components Of the Northwest Hui Group Revealed Using Aisnpssupporting
confidence: 90%
“…Additionally, our previous research based on the complete mitochondrial genome illustrated that the Northwest Hui group typically exhibited closer genetic relationships with East Asian populations, roughly concordant with the genetic result provided by 55 AISNPs in this study (Chen et al, 2020). Briefly, our previous study indicated that the genetic component of the maternal lineage that appeared in the Northwest Hui group might be predominantly derived from East Asia (Chen et al, 2020); the Y chromosome strictly follows the paternal inheritance with little recombination during the genetic process, so the paternal lineage of the Northwest Hui group may still retain some ancient genetic imprints closely related to Central or West Asian populations (Gladney, 1998). Considering the ancestral component prediction, the Northwest Hui group revealed a large proportion of ancestral components from East Asia and relatively little from Europe.…”
Section: Ancestral Components Of the Northwest Hui Group Revealed Using Aisnpssupporting
confidence: 90%
See 3 more Smart Citations